Cliché Humanitarianism: Migrant Gazes at the Rhetoric of Dangerous Pity in We Need New Names and Americanah (2022)
Due to their intermediate condition of cultural translator, the migrant subject presents an ambiguous perspective on the clichés of humanitarianism. The protagonists in We Need New Names and Americanah are able to relate their experiences with humanitarian aid, while migration distances them from this condition, due to their origins, leading to a critical and ironically condemnatory voice about the paradoxes of piety. At the same time, their settlement in the host country disorients them and makes them progressively lose their ability for making penetrating reflections, turning them into consumers of suffering from a distance and reinforcing the coloniality of power. First, we look at the uprooting of migrant subjects, Ifemelu and Darling; this is followed by a discussion on the evolution of the politics and the paradoxes of pity and their influence on the spectacle of suffering from the gaze of the migrant subject; and finally, we examine the artifice of cliché humanitarianism in the media and photography, and its relationship with NGOs.